A relevância do conhecimento histórico das Ginásticas na formação e atuação do profissional de educação física - Figueiredo, Juliana Frâncica [UNESP]; Hunger, Dagmar Aparecida Cynthia França [UNESP] (My University, 2010)
The Gymnastics, in its extensive historical background, were part of the reasoning in the area now known as Physical Education. Deepening the knowledge from the historical Gymnastics during his education is extremely important for professional performance in Physical Education, as this knowledge can serve as a tool for the current configuration of the Gymnastics. Thus, this study presents a review of the literature that you want the frontline of the importance of historical knowledge Gymnastics during his education, is looking ahead to fetch reflect the current format of the same from an informed historically built as it is from the preservation of the knowledge that will be legitimized new avenues for the development of Gymnastics.
The relevance of historical knowledge of Gymnastics in the formation and operation of physical education professional
Keywords: Gymnastics; History; Knowledge